Changing adherence-related beliefs about ICS maintenance treatment for asthma: feasibility study of an intervention delivered by asthma nurse specialists. Issue 6 (5th June 2015) - Chapman, Sarah C E; Barnes, Neil; Barnes, Mari; Wilkinson, Andrea; Hartley, John; Piddock, Cher; Weinman, John; Horne, Rob
Abstract : Objectives: The Necessity-Concerns Framework (NCF) posits that non-adherence to inhaled corticosteroids (ICS) in asthma is influenced by doubts about the necessity for ICS and concerns about their potential adverse effects. This feasibility study examined whether these beliefs could be changed by briefing asthma nurse specialists on ways of addressing necessity beliefs and concerns within consultations. Design: Pre-post intervention study. Setting: Secondary care. Participants: Patients with a diagnosis of moderate to severe asthma who were prescribed daily ICS were recruited to either a hospital care group (n=79; 71.0% female) or intervention group (n=57; 66.7% female). Intervention: Asthma nurse specialists attended a 1.5-day NCF briefing. Primary and secondary outcome measures: Beliefs about ICS (primary outcome) and self-reported adherence were measured preconsultation and 1 month postconsultation. Participants also rated their satisfaction with their consultations immediately after the consultation. Consultation recordings were coded to assess intervention delivery. Results: After the NCF briefing, nurse specialists elicited and addressed beliefs about medicine more frequently. The frequency of using the NCF remained low, for example, open questions eliciting adherence were used in 0/59 hospital care versus 14/49 (28.6%) intervention consultations. Doubts about personal necessity for, and concerns about, ICS were reduced at 1 month postbriefing (p<0.05), but the intervention was not applied extensively enough to improve adherence. Conclusions: The intervention changed nurse consultations, but not sufficiently enough to fully address non-adherence or adherence-related ICS beliefs (necessity and concerns). More effective techniques are needed to support nurse specialists and other practitioners to apply the intervention in hospital asthma review consultations.